Heat acclimatization and exertional heat illness prevention in youth football programs - Poole, J. A.; Stearns, R. L.; Lopez, R. M. (Strength and Conditioning Journal, 2017)
Athletes are at an increased risk of experiencing an exertional heat illness (ehi) due to the physical exertion required by football, particularly when performed in hot and humid conditions. Various modifications together with education and preparation by those working with youth football athletes can help mitigate the risks of exercising in the heat. The overall ehi risk for youth athletes is not well known. The purpose of this article is to review the existing literature regarding thermoregulation of younger athletes and to provide guidelines for coaches and clinicians on how to prevent ehi for safer participation in youth football.